Meghdutam and Nature: A Comparative Study on Nature, Ecocriticism and Transcendentalism between Kalidasa and Ralph Waldo Emerson (Sudurpaschim Spectrum, 2024)
Kalidasa is known as the most powerful nature poet of Sanskrit. His depth of knowledge about nature and his true love for it make him one of the best Indian poets. By describing different seasons, natural elements like trees and plants, animals and birds, clouds, mountains, fountains and many things, Kalidasa helps the readers to realize the beauty of nature. On the other hand, Ralph Waldo Emerson, the great philosopher and poet of eighteenth century has some philosophical ideals where nature is not simply a backdrop but an essential element of human consciousness and love. Meghdutam is such kind of a love poem by Kalidasa where he uses the beauty and importance of nature, and a beautiful connection between man and nature. Emerson’s philosophy on nature is found in the lines of Kalidasa. In brief, Emerson has many philosophical concepts about nature of his own which can be applied in Meghdutam. This article explores how the incessant environmental beauty of Meghdutam brings a beautiful realization about the importance of nature in human life in the light of Emerson’s philosophical concepts of nature. A deep connection between nature and human experience in Kalidasa's Meghdutam is explored examining its resonance with Emerson’s philosophy of Nature. Through this article, my intention is to confirm that both Kalidasa and Emerson highlight the transformational influence of nature, advocating for a profound ecological and spiritual bond between people and the environment.